Eficácia de um flavonoide (fisetinidol) obtido do caule de Bauhinia pulchella e seu derivado semi-sintético (palmitato de fisetinidol) em um ensaio pré-clínico de periodontite em ratas - Pinto, Isabela Ribeiro (2019)
Periodontitis is a inflammatory disease that culminates in tooth loss. Its pathogenesis of periodontitis involves the presence of bacteria and the immune/inflammatory host response, whose interaction may determine the generation of inflammatory mediators, including cytokines, nitric oxide and reactive oxygen species, which amplify and perpetuate the inflammatory response. Many species of the Bauhinia genus are used in folk medicine because of their anti-inflammatory activities anti-inflammatory, analgesic and antioxidant. Several classes of compounds have been isolated from Bauhinia species, especially flavonoids. Fisetinidol, flavonoid of the class of flavan-3-ol, is a secondary metabolite obtained from the stem of the ethanolic extract of Bauhinia pulchella. From Fisetinidol, a semi-synthetic derivative, (-)-fisetinidol palmitate, was synthesized by our research group. Therefore, the aim of this study are to evaluate the efficacy of Fisetinidol and (-)-fisetinidol palmitate in a model of periodontitis in Wistar rats. Periodontitis were induced in Wistar rats by placing a nylon thread ligature around second upper left molars and treated (per os) once a day during 11 days with Fisetinidol (0,0001 or 0,001 mg/kg) or (-)-fisetinidol palmitate (0,01 or 0,1 mg/kg) or vehicle (saline). At the 11th day, the animals were terminally anesthetized and the maxillae were excised for morphometric analysis using ImageJ® software. The gingival tissue were collected to quantify the IL-1β, IL-8/CINC-1 levels (ELISA); superoxide dismutase, catalase, nitrite/nitrate (spectrophotometric assay); and analysis of genetic expression IL-6, RANK, and OPG (qRT-PCR). Also, samples from peripheral blood samples were collected to evaluate bone-specific alkaline phosphatase, and transaminases and creatininae dosages. The parametric data were analyzed by (ANOVA) and Tukey or Games-Howell. For non-parametric data, the results were expressed in median and evaluated by the Kruskall-Wallis test followed by the Dunn's test (p <0.05). Fisetinidol (0.0001 or 0.001 mg/kg) and (-)-fisetinidol palmitate (0.1 mg/kg) significantly reduced alveolar bone loss. (-)-fisetinidol palmitate (0.1 mg/kg) decreased IL1-β and IL-8 / CINC-1, nitrite/nitrate levels and increased SOD and CAT activity. It was also able to reduce the gene expression of IL-6, RANK and increased the expression of OPG. Statistical differences (p> 0.05) were not observed in the ALT, AST and FAT between the groups. These results suggest that Fisetinidol and (-)-fisetinidol palmitate reduced alveolar bone resorption in a pre-clinical periodontitis assay, and that the likely mechanism of action of (-)-fisetinidol palmitate occurs through the reduction of inflammatory mediators and oxidative stress.